(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Managerial overconfidence is an interesting topic to study. Overconfidence can be caused by the success of a company leader. Overconfidence affects the managerial actions and strategic policies taken by companies, especially in investment. This study aims to examine the effect of overconfidence calculated by using capital expenditure and investment opportunity set calculated by using Market Book Value Equity (MBVE) on firm value calculated by Tobin’sQ with capital structure as an intervening variable calculated by Debt to EquityRatio (DER). 232 open manufacturing industries in Indonesia and 120 open manufacturing companies in Malaysia in the period of 2016-2019 were taken as the samples by using purposive sampling technique. In this study, the data were analyzed by using Eviews 10. This study confirms that there is an effect of overconfidence on firm value intervened by the capital structure in open manufacturing industries in Indonesia and Malaysia. Meanwhile, the capital structure variable cannot intervene in the investment opportunity set variable onthe firm value in open manufacturing industries in Indonesia and Malaysia.